Pembuatan Aplikasi Perwalian Online Berbasis Android dan Web - Soedjarwo, Stefanus Christianto; -, Liliana; Gunawan, Ibnu (Jurnal Infra, 2015)
Along with the development of Petra Christian University, the number of students and teachers will increase too. Petra Christian University would need a means to communicate among students and lecturers, especially on academic advisory. Technology has an important role as tool to communicate on academic advisory. By utilizing technology for academic advisory, it will be easier, faster and more flexible since there is no restriction on place and time. With the technology, recording data on digital server will also increase administration efficacy.Therefore, this thesis tries to make an application that can help academic advisory process and record it to database. Using MySQL database as database storage will increase performance.Some tests have been made on the Android and Web based academic advisory application. The application can be used to do academic advisory by internet with smartphone or web browser as tool. Recordings also work well for all academic advisory by students and lecturers.